The Effect of Offline Learning Model Assisted in Practicum Discovery Learning on Learning Outcomes - Azizah Azizah; Siti Fajeriah (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
The purpose of this article was to determine the effect of the offline learning model assisted by the Dilan practicum module on hot material on the learning outcomes of fifth-grade students of SD Inpres 1 Ujuna. This type of research is quantitative research with the type of experimental research using the Quasi-experimental method with the Nonequivalent Control Group Design design. The subjects in this study were fifth-grade students of SD Inpres 1 Ujuna. Data collection was carried out using multiple-choice questions, and data analysis used prerequisite tests, namely normality and homogeneity tests and hypothesis testing using independent sample t-test tests which were analyzed using SPSS Statistics version 16. Based on the results of this study, a significant value of 0.001 < 0, 05 then accept the hypothesis Ha and reject Ho, meaning that the Dilan practicum module has an effect when used in improving student learning outcomes. So it can be concluded that there is an effect when using the offline learning model assisted by Dilan's practical module on hot material on the learning outcomes of fifth-grade students of SD Inpres 1 Ujuna.